Anti-inflammatory and anti-rejection effects of herbal medicine ingredients in organ transplantation: a systematic review and meta-analysis - Lin, Jingru; Wu, Zhennan; Liu, Huazhen; Qiu, Feifei; Dai, Zhenhua (Frontiers in Immunology, 2025)
BackgroundAlthough postoperative rejection in transplant patients can be managed with immunosuppressants, their use is associated with some complications due to excessive immunosuppression. Recent animal studies in allotransplantation have suggested that certain ingredients of Chinese herbal medicine can extend transplant survival. However, their effects on transplantation have not been systematically reviewed and analyzed. The aim of this study was to evaluate the effects of herbal medicine ingredients on complications and survival of transplanted organs after heart, liver and kidney transplantation, and to explore the possible mechanism of action.Materials and methodsDatabases, including PubMed, EMBASE, Cochrane Library, Web of Science, Wang Fang, China National Knowledge Infrastructure (CNKI), China Science and Technological Journal Database (VIP) and Chinese Biomedical Literature Database (CBM), were searched up to January 1 2025. Animal studies reporting the effects of Chinese herbal medicine ingredients (HMIs) on postoperative complications and organ transplant survival/outcome were included. Methodological quality was assessed using the SYRCLE risk of bias tool. Meta-analysis was performed using R 4.3 software to assess levels of inflammatory factors, oxidative stress markers, apoptosis markers, indicators of liver/kidney function, median graft survival time and immune cell subsets.Results and conclusionsA total of 18 studies, involving 357 rodents were included. The overall quality of the included reports was moderate. We found that HMIs enhanced organ graft survival by reducing the Banff score, extending the median survival time (MST), and exerting anti-inflammatory, antioxidant and anti-apoptotic effects. HMIs can also inhibit T cell proliferation, dendritic cell (DC) maturation and increase the proportion of CD4+ regulatory T (Treg) cells. Furthermore, the improvement in liver and kidney function indicators, such as alanine aminotransferase (ALT), aspartate transaminase (AST), Serum creatinine (Scr) and blood urea nitrogen (BUN) also suggested protective effects of HMIs on liver and kidney function. However, the high heterogeneity observed in several analyses highlights the need for standardized experimental designs and further studies to confirm these findings and to explore their underlying mechanisms. Thus, our meta-analysis indicates that HMIs improve transplantation outcomes in animal models. These results lay a solid foundation for translating HMIs into clinical strategies for improving transplantation outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251002755, identifier crd420251002755.